2020
DOI: 10.3390/ijerph17134654
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Application of Drought Characteristics Based on Theory of Runs and Copulas in Yunnan, Southwest China

Abstract: Drought is a complex natural disaster phenomenon. It is of great significance to analyze the occurrence and development of drought events for drought prevention. In this study, two drought characteristic variables (the drought duration and severity) were extracted by using the Theory of Runs based on four drought indexes (i.e., the percentage of precipitation anomaly, the standardized precipitation index, the standardized precipitation evapotranspiration index and the improved comprehensive meteorological drou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…On the other hand, Yunnan Province has become a hot spot of drought in Southwest China [37]. More articles focus on the analysis of drought changes and causes in Yunnan Province [27][28][29][30]38,39]. The severity and frequency of drought in Southwest China have increased in recent years, and drought events have become more frequent in the 21st century as can be seen by analyzing the spatiotemporal variation of SPEI and SRI, which is consistent with conclusions obtained by previous studies [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Yunnan Province has become a hot spot of drought in Southwest China [37]. More articles focus on the analysis of drought changes and causes in Yunnan Province [27][28][29][30]38,39]. The severity and frequency of drought in Southwest China have increased in recent years, and drought events have become more frequent in the 21st century as can be seen by analyzing the spatiotemporal variation of SPEI and SRI, which is consistent with conclusions obtained by previous studies [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Run length theory is a method to analyze time series, which was initially applied to drought research by Herbst [22]. In this study, run length theory was used to extract two characteristic variables of drought severity and drought duration, The basic operation is as follows [20] (Figure 2):…”
Section: Drought Feature Recognitionmentioning
confidence: 99%
“…There are more than 20 copula functions in the toolbox which can be used for fitting. In this paper, three commonly used symmetric copula functions were selected, namely, Clayton copula, Gumbel copula and Frank copula [18,20] (Table 2). Finally, the selected functions were tested for goodness of fit to determine the optimal copula function, and the test methods were NSE and RMSE.…”
Section: Construction Of Copula Joint Distribution Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…He et al [31] used the run theory to identify the frequency, duration, severity, and intensity of all droughts in China on the basis of the monthly percentage of the precipitation anomaly rate index and found that China has five obvious meteorological drought-prone areas. These studies have shown that the run theory method can effectively identify and detect the temporal characteristics of drought [34,35]. Hence, determining whether the run theory can effectively and efficiently detect temporal drought features from SPEI sequences is an interesting topic.…”
Section: Introductionmentioning
confidence: 99%